ADAPTATION OF THE LYMPHOCYTE CULTURE TECHNIQUE OF ALPACAS AND LAMAS FOR THE ANALYSIS OF SISTER CHROMATID EXCHANGE (SCE) - Ramos G., Mariella (2014)
The study describes the changes made to adapt the lymphocyte culture technique and the analysis of sister chromatid exchange (SCE ) for South American camelids in the Laboratory of Human Genetics, San Marcos University, Lima, Peru used in the University of Naples and the National Research Centre (CNR- ISPAAM), Italy. Blood samples were collected from 8 alpacas and 19 llamas from Puno and Huancavelica, both sexes, and approximately 5 years old. The results allowed visualizing lymphocyte cells dividing and a mitotic index average of five metaphases per field observed at 100X. The adapted technique is considered of simple application, allowing to estimate the frequency of SCE securely and unambiguously, and it is supported by differential staining of sister chromatids with Giemsa or fluorochrome when incorporated 5-BrdU for two consecutive cell cycles.